2014
DOI: 10.1021/cm503061g
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium Nanoparticle Anchoring on AlPO4 for Efficient Catalyst Sintering Suppression

Abstract: Rhodium catalysts exhibited higher dispersion with tridymite-type AlPO 4 supports than with Al 2 O 3 during thermal aging at 900 °C under an oxidizing atmosphere. The local structural analysis via X-ray photoelectron spectroscopy, transmission electron microscopy, X-ray absorption fine structure, and infrared spectroscopy suggested that the sintering of AlPO 4supported Rh nanoparticles was significantly suppressed because of anchoring via a Rh−O−P linkage at the interface between the metal and support. Most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(79 citation statements)
references
References 40 publications
14
65
0
Order By: Relevance
“…This result is consistent with the experimental suggestion that Rh particles adsorb at the PO site. 15,17 Table 1 also shows that the deformation energy of the surface is considerably high in all adsorption structures, whereas the deformation energy of the Rh 2 is extremely small in all cases. Although the interaction energy between the Rh 2 and the AlO hy site is considerably large, the deformation energy of the surface is also extremely large at this site, which is the reason for the small binding energy of the Rh 2 adsorption at the AlO hy site.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…This result is consistent with the experimental suggestion that Rh particles adsorb at the PO site. 15,17 Table 1 also shows that the deformation energy of the surface is considerably high in all adsorption structures, whereas the deformation energy of the Rh 2 is extremely small in all cases. Although the interaction energy between the Rh 2 and the AlO hy site is considerably large, the deformation energy of the surface is also extremely large at this site, which is the reason for the small binding energy of the Rh 2 adsorption at the AlO hy site.…”
Section: Resultsmentioning
confidence: 88%
“…31 In addition, Machida's group reported that the partial dehydration occurs by increasing the temperature. 17 In the partially dehydrated surface, three types of adsorption structure are possible, depending on the manner of partial dehydration. In one structure, the Rh dimer interacts with the dehydrated PO site, which is near the dehydrated Al uns atom, as shown in Figure 2B.…”
Section: Models Methods and Computationalmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously studied various metal phosphates, such as AlPO 4 , ZrP 2 O 7 , and LaPO 4 , as thermally stable supports for Rh catalysts [11][12][13][14][15][16][17][18][19]. These materials produce optimum interactions with the Rh species via Rh O P bonding and enable high dispersion of Rh anchored onto the phosphate unit on the surface [13,14,17]. The interface Rh O P bonding also affects the electronic states and redox behaviors of Rh; Rh oxide (Rh 2 O 3 )…”
Section: Introductionmentioning
confidence: 99%